Discourse phronesis in organizational change: a narrative analysis. Issue 5 (5th August 2014) - Jansson, Noora
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine how discursive practices are involved in organizational change. Design/methodology/approach – This research scrutinizes organizational change by combining discourse and practice approaches. A case study at a public university hospital is conducted with a narrative analysis method. Findings – The key finding of this research is that discursive practices are involved in organizational change through discourse phronesis. Discourse phronesis is a socially and contextually developed phenomenon, and hence discursive practices are particular within context. The case study revealed four particular discursive practices as examples of discourse phronesis: field practices, mandate practices, priority practices and word practices. Practical implications – The results of this research advance awareness of the concealed power within discursive practices and, more importantly, invite practitioners to pursue the intellectual virtue of discourse phronesis while implementing organizational change. Discourse phronesis may be utilized as a gateway to advance change goals and to translate various discourses and actions that otherwise might remain unexplained. Originality/value – Although extensively studied, organizational change has not previously been directly approached through discourse phronesis, and by doing so this empirical research provides novelty value to both organizational change research and discourse analysis. By introducing the concept of discourse phronesis, this research offers scholars an alternative lens, the intellectual practicality lens, through which to approach organizational change and perhaps to develop new understandings of the great challenges that organizational change complexities usually generate.